AB0323 Household Work Disability of Moroccan Housewives with Rheumatoid Arthritis. (10th June 2014) - Ben Slama, I.; Allali, F.; El Kabbaj, S.; Lakhdar, T.; Medrare, L.; Ngeuleu, A.; Rkain, H.; Hajjaj-Hassouni, N.
Abstract : Objectives: There have been few studies on the impact of rheumatoid arthritis (RA) on the work of the household. Our study aims to evaluate the impact of rheumatoid arthritis (RA) on women in Moroccan home. Methods: Demographic data, clinical and biological characteristics of the disease were collected. Depression was assessed by HAD questionnaire (Hospital Anxiety and Depression Scale). Working from home has been assessed by a multiple choice questionnaire [1] (no problems, some problems, many difficulties and disabilities) on the following items: the ability to do household chores, cleaning the house, washing floor, washing the dishes, cooking, and caring for children and husband. Women who failed to achieve at least one household activity were considered unable to domestic work and they were compared to those who have no such disability. Univariate and multivariate logistic regression was performed to identify factors associated with this disability for domestic work. Results: 90 women (mean age 49.7±11.4 years) with Rheumatoid arthritis were included. The disease's median duration was 8 years [4, 14], the median of DAS28-ESR was 4.27±1.75 and median of HAQ was 0.5 [0, 1, 37]. The inability to domestic work was found in 31 patients (34.5%), this inability related to the following items: do household activities (23.3%), clean the house (26.7%), wash the floor (34.4%), caring for children and husband (14.4%), washing dishes (26.7%) and cook ( 17.8%). In univariate analysis the inability of domestic work was associated with high disease activity (OR =2.23, p<0.0001), a significant pain intensity (OR =1.03, p=0.001), with morning stiffness prolonged (OR =1.015, p=0.005), a significant functional impairment (OR =7.25, p<0.0001) and depression (OR =1.09, p=0.003). After multivariate analysis, factors that remained significantly associated with the inability of domestic work were higher HAQ (OR =6.72, p<0.0001) and DAS28 - ESR increased (OR =2.05, p=0.003). Conclusions: We conclude that RA is highly predictive of homemaking disability in moroccan women, especially those with active RA and significant functional impairment. References: Household work disability of Arab houseswives with rheumatoid arthritis. Clin Rheumatol. 2007. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5812